Validating a model of organizational citizenship behavior from Islamic perspective for Indonesian Islamic higher education institutions: a structural equation modeling approach - Mohd Ali, Hairuddin; Shohib, Muhammad Wildan; Ibrahim, Mohd Burhan (IIUM Press, 2021)
This study aims to validate and confirm a structural equation modeling (hypothesized model) of organizational citizenship behavior from Islamic perspective (OCBIP) practices in Indonesian state Islamic higher education institutions. This study employed a quantitative survey method to collect the data from 450 academic staff of six States Islamic Higher Education Institutions across Indonesia using a five-point organizational citizenship behavior scale based on Islamic perspective. A descriptive analysis technique was performed to comprehend the respondents view on the practice of underlying factor, followed by the application of confirmatory factor analysis and full-fledge SEM. The study’s findings exhibited that the academic staff in the sampled higher institutions of learning had high inclination and passion for practicing OCBIP in their respective working place. Results also showed a high degree of OCBIP practices by academic staff in selected higher education institutions. Theoretically, the study also established a four factor model of OCBIP practices such as altruism, civic virtue, advocating high moral standards (da’wah), and removing harm (raf’al haraj). The result was deliberated through SEM on the observed instruments, and the hypothesized model of OCBIP under the study was empirically valid and reliable. The findings provided a remarkable contribution for institutions of higher learning and top management to intensify the operation of OCB based on Islamic perspective in Higher Education Institutions (HEIs). The practical contributions guide the academic staff, particularly in Indonesian state Islamic higher education institutions and other regions, to embrace all principal human resource development and management practices. The study has successfully tested, formulated, and validated the hypothesized model of organizational citizenship behavior based on the Islamic perspective for Indonesian State Islamic Higher Education Institutions.